Jember Fashion Carnival: Konstruksi Identitas dalam Masyarakat Jaringan - Jannah, Raudlatul (UI Scholars Hub, 2012)
This research focuses on the construction of Jember city identity in the network society era. This research revealed that the construction process of Jember city identity is complex. By using Manuel Castells’ theory about territorial identity especially in network society, this paper intends to interpret Jember Fashion Carnival (JFC) as a project identity in the discourse of network society. The findings show that JFC does not only negotiate Jember city identity but also practice logic of network society. It can be seen by the way that media can change JFC as a fashion carnival into a project of Jember city identity, and then transform it to financial capital as entertaining carnaval performed in various cities. Logic of networks have the ability to transform resources to be more profitable. But, how to internalize this idea to Jember cultural space that it recognized by all citizens is still a problem. Finally, how the end of this process is, and whether world city carnival will be a new identity of Jember, will be unveiled by time.